ECOSYSTEM ORIENTED APPROACH TOWARDS DEVELOPMENT OF FISHERIES IN PONG RESERVOIR, HIMACHAL PRADESH - KAUSHAL, D K; Kumar, S (Journal of the Inland Fisheries Society of India, 2016)
Pong reservoir’s limno-chemical features and productivity status were assessed from 1991 to 1995. The range of total alkalinity (48 to 110 mg l-1), temperature (13 to 330C), pH (6.8 to 8.3) and specific conductivity (96.4 to 266.8 μmhoscm-1) exhibited medium productivity of the reservoir. The reservoir has both thermal and chemical stratification. Annual yield of the reservoir has gradually decreased from 53 kg ha-1 in 1987-88 to 24.7 kg ha-1 in 1994-95. Average production potential of the reservoir is 118 kg ha-1. The analysis of catch statistics in the light of prevailing ecological conditions suggest the need for eco-friendly fishery management to augment fish production.